THE URGENCE OF RECHTERLIJK PARDON REGULATION IN CRIMINAL LAW RENEWAL - Vincentius Patria Setyawan; Itok Dwi Kurniawan (Jurnal Inovasi Penelitian, 2021)
ABSTRACT The principle of legality in Indonesia has characteristics that are so rigid in providing a basis that legitimizes the imposition of criminal sanctions. Based on the principle of legality, every act that fulfills the elements of a criminal act can be punished (strafbaar). This of course only shows aspects of legal certainty in the imposition of criminal sanctions, and on the contrary will cause disturbances to the sense of justice for the community. This article discusses the judge's pardon which is ideal to be applied to minor crimes. This judge's pardon looks more at the sociological aspect of the imposition of a crime, which focuses on balancing the interests of the perpetrators and victims of crime.